Banking Competition On Investment Efficiency of Non Financial Companies in Indonesia - Ferris Hosema Putra; Vina Nugroho (Universitas Pelita Harapan, 2025)
The structure of the banking market influences corporate investment efficiency through credit allocation, where the level of banking competition determines the quality of credit screening and capital allocation. This study aims to examine the impact of banking competition on the investment efficiency of non-financial firms listed on the Indonesia Stock Exchange during the 2013–2023 period. The banking market structure is measured using three key indicators: Top 3 Bank Assets (TOP), the Herfindahl-Hirschman Index (HHI), and the Lerner Index. Data is processed using the Generalized Method of Moments (GMM) with a two-step system estimation and robust standard errors. Additionally, diagnostic tests (AR(1), AR(2), Sargan-Hansen) and robustness checks were conducted by removing dummy control variables. The results show that the TOP and HHI indicators have significantly negative coefficients on investment efficiency, indicating that a more concentrated banking market leads to more efficient corporate investment allocation. Although the Lerner Index also shows a negative coefficient, its influence is relatively weak in supporting the alternative hypothesis. These findings suggest that a more centralized banking structure can enhance credit monitoring mechanisms and improve investment efficiency in Indonesia.